Penampilan Morfologi Akar Beberapa Hasil Persilangan (F1) Tanaman Jagung Pada Media Tanam Tanah Gambut Dengan Penambahan Bahan Organik Leguminosa Di Rhizotron - Wita Purwasih; Khairunnisa lubis; Eva Sartini Bayu (Universitas Sumatera Utara, 2019)
The maize in indonesia mostly use land that is not fertile. The objective of the research was identified the selection character based on root morphology of hybrid maize (F1) in peat soil medium applicated with legume organic manure in rhizotron. The research was conducted at the greenhouse of Faculty of Agriculture, University of Sumatera Utara, from February until July 2017. The Randomized Block Design was used with two factors, the first factor is the population (V1, V2, V3, V4, V5) and the second factor is the planting medium (peat soil, peat soil + leucena, peat soil + mucuna). The parameters observed were: the number of root, the length of root, the diameter of root dispersed, the fresh weight of the canopy, the fresh weight of root and the dry weight of root. The result showed that the population F1 significantly affected the number of root, the volume of root, the fresh weight of root and the dry weight of root. The planting medium significantly affected the number of root, the length of root, the diameter of root dispersed, the volume of root, the fresh weight of the canopy, the fresh weight of root, the dry weight of root. Interaction between the population F1 NEI9008 x CLA46 (V5) and the planting medium peat soil + mucuna significantly affected the fresh weight of root. Keywords : maize, legume organic manure, peat soil, root morphology, rhizotron